الشرح اللغوي للحديث النبوي من خلال كتاب عمدة القاري شرح صحيح البخاري لبدر الدين العيني - دراسة نماذج مختارة - حدد محمد; بن تيشة أحمد (University of Eloued جامعة الوادي, 2024)
"الحمد لله ربّ العالمين، والصلاة والسّلام على أشرف المرسلين، سيدنا محمد، وعلى آله وصحبه أجمعين، في بحثنا المتواضع والمختصر بعنوان الشرح اللغوي للحديث النبوي من كتاب عمدة القاري شرح صحيح البخاري لبدر الدين العيني، وتتمحور هذه الدراسة على الإشكالية التالية: ما دور اللغة في شرح الحديث النبوي وكيف وضفها الإمام العيني في كتابه عمدة القاري ؟، تمت الإجابة عن هذه الإشكالية في هذه المذكرة، التي اِنْبَنَتْ على مقدمة، ومبحثين، وخاتمة؛ حيث خصصنا المقدمة للتعريف بالموضوع وأهميته، دوافع اختياره، أهداف اليحث، الجهود السابقة، ومنهج البحث. أمّا المبحث الأول فقد عُني بالجانب النظري للدراسة، تناولنا فيه التعريف بمصطلحات الموضوع لغة واصطلاحا، نشأة الشرح اللغوي للحديث النبوي، أهمية اللغة في شرح الحديث، والضوابط والمعايير التي وضعها علماء الحديث لشرح الحديث لغويا. أمّا المبحث الثاني فخصصناه للجانب التطبيقي وذلك بالتعريف بالإمام العيني وثقافته اللغوية وكتابه عمدة القاري، ومنهجه المتبع في الشرح، وأخيرًا سقنا أمثلة موجزة من شرحه للسند والمتن لغويًا. وقد خلصت هذه الدراسة بنتائج أهمها: امكانية الاستدلال والاحتجاج اللغوي بالحديث النبوي، كما أن الإمام العيني من خلال كتابه هذا أبدع وتميز عن غيره في هذا الشرح بطريقته التي لم يسبقه أحد إليها، وهي توظيف اللغة في شرح الحديث سندًا ومتنًا." Thank God, Lord of the Worlds, prayer and peace for the distinguished senders, our Lord Muhammad, and for all his gods and companions, in our humble and brief paper entitled The Language Explanation of the Prophetic Speech from the Book of the Mayor of the Continental Shelf, which correctly explained the steamingness of Badr al-Din al-Aini. This study is focused on the following problem: What is the role of language in explaining the Prophetic talk and how is it included in his book by the Secretary-General? This problem has been answered in this note, which was based on an introduction, two researchers and a conclusion; we have devoted the introduction to defining the subject and its importance, the motives of his choice, the objectives of his research, previous efforts, and the approach to research. The first research was concerned with the theoretical aspect of the study, in which we addressed the definition of terms of the topic in language and terminology, the origin of the linguistic interpretation of the prophetic discourse, the importance of the language in explaining the talk, and the parameters and criteria developed by modern scientists to explain the language. The second research was devoted to the application side by introducing the Special Front, its linguistic culture and its book as the Mayor of the Continental, its approach to the commentary, and finally providing brief examples of its explanation of the . The most important findings of this study are: the possibility of linguistic reasoning and protest by the Prophet; and through this book, the imam is more creative and distinguished than anyone else in this explanation in his unprecedented way of using the language to explain the conversation. "
Keywords: الشرح، اللغوي، الحديث، عمدة القاري، بدر الدين العيني .; explanation; language; modern; continental mayor; Badr al-Aini.